A study of prognostic score for predicting the outcome in cases of traumatic brain injury - Singh Pal, Sudhir; Rathore, Ashay (International Surgery Journal, 2020)
Background: Glasgow coma scale (GCS) and the Glasgow outcome scale help us with confident predictions after 24 h following the injury, but not on admission. The IMPACT and CRASH studies provided new methods for performing prognostic studies of traumatic brain injury. And this prognostic scoring system has been studied in our study. Methods: This is an observational prospective cohort study performed at the department of surgery, Gandhi medical college and Hamidia hospital, Bhopal on 87 patients during a period of 2 years. A preformed pro-forma was filled for each patient after 6 hours of resuscitation which included all the details of the patients like name, age, sex, CR no., and GCS after resuscitation, mode of injury, the clinical evaluation score used by IMPACT trial and neurological finding, management details, CT scan was done as soon as possible for all patients and findings were included in the pro-forma. The final outcome was recorded at the time of discharge. Results: Among Patients with mean total prognostic score of 0-4, 97% patients discharged without deficit, 3% discharged with deficit with no mortality. Among score of 15-20, only 7 % can be discharged without deficit and 7% could be discharged without deficit, while 86 % patient died. Conclusions: The mean total prognostic score of discharged groups was significantly lower than the patients in discharged group. We concluded that this prognostic model helps us to individually identify patients who will succumb to death and early need for surgical intervention.